Innovation Management Approach - Sarnoto, Ahmad Zain; Ahariani, Dwi Eka; Saihu, Made (Educational Journal of Islamic Management, 2025)
Innovation in Islamic education is a necessity in facing the challenges of globalization and rapid technological advances. This article analyzes innovation management approaches applied in the context of Islamic education, including curriculum, human resources, technology and community-based approaches. The research aims to explore and compare the effectiveness of each approach in creating change and improving the quality of education. Using qualitative analysis methods, data collected from various Islamic education institutions were analyzed to evaluate the impact of each approach on student learning outcomes and the relevance of education in contemporary society. The research findings show that although each approach has advantages and disadvantages, the integration of the various approaches can provide more optimal results in improving the quality of education. The article concludes with recommendations for the application of more adaptive and collaborative innovation management approaches in the future, in order to strengthen the role of Islamic education in shaping a generation that is intelligent, moral and ready to face global challenges